Kajian Ekonomi Perbandingan Antara Beli dan Sewa Alat Gali Muat dan Alat Angkut pada Penambangan Batu Pasir Perusahaan Perorangan H. Adin Sumarna di Desa Sarimukti, Kecamatan Citatah, Kabupaten Bandung Barat, Provinsi Jawa Barat - Rismul Rasyad Rasyad; Zaenal; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2022)
Perusahaan Perseorangan atas nama H.ADIN SUMARNA, which plans to use the SUMITOMO digging tool SH-210 type and HUTO haulage type DUTRO 130MDL for the activity of digging, loading and transporting sand material, to determine the selection of the loading and unloading digging equipment and conveyance that has the most economical supply the economy. CV Bumi Pasir Makmur which has 2,632,821 tons of mined reserves, with a planned production target of 460,000 tons / year with an effective working time of 6.5 hours / day or 1,931 hours / year. The need for the number of loading and unloading equipment and conveyances to meet production targets is carried out by calculating the productivity and Macth Factor values of the equipment to be used. The productivity value is 264.67 tons / hour or 510,953 tons / year for loading and unloading equipment and 131.78 tons / hour / unit or 254,405 tons / year / unit for transportation, so the amount of loading and unloading equipment needs 1 (one) unit and tool transport 2 (two) units with an alignment value of 1 (one) which means perfect. The costs that have to be incurred by Perusahaan Perseorangan atas nama H.ADIN SUMARNA for the need for loading and unloading equipment and transportation equipment for production which includes equipment procurement costs, operational costs, and operator salary costs. The cost for procurement of equipment by purchase is Rp. 2,115,300,000 and rental fee is Rp. 849,600,000 / year. The operational cost of the equipment is Rp. 1,137,240,248/year and the lease is Rp. 1,065,240,248/year. Operator salary costs as much as Rp. 129,360,000 / year. The cost of producing unloading and loading and buying conveyance equipment is IDR 1,266,600,248/year and rent is IDR 2,044,200,248/year. Economic analysis of loading and unloading equipment and conveyances with a value of inflation of 3% / year shows the cumulative value of NPV in purchase of Rp. 712,271,102,963 and a rental of Rp. 695,245,976,224 with a difference of Rp. 17,026,129,738. IRR value of 63.53 for purchase and 63.73 for rent with a difference of 0.2. PBP value of purchase is 1.58 and rent is 1.56 with a difference of 0.02. Perusahaan Perseorangan atas nama H.ADIN SUMARNA dalam kegitanan penambangan yang merencanakan penggunaan alat gali muat pabrikan SUMITOMO tipe SH-210 dan alat angkut pabrikan HINO type DUTRO 130MDL untuk kegiatan gali, muat, dan angkut material pasir. Penentuan pemilihan penggunaan alat gali muat dan alat angkut yang efektif dan efisien dilakukan perhitungan dan kajian ekonomi. Perusahaan Perseorangan atas nama H.ADIN SUMARNA yang memiliki cadangan tertambang 2.632.821 ton, dengan rencana target produksi 460.000 ton/tahun dengan waktu efektif kerja 6,5 jam/hari atau 1.931 jam/tahun. Kebutuhan jumlah alat gali muat dan alat angkut untuk memenuhi target produksi dilakukan perhitungan produktifitas dan nilai keserasian/Macth Factor dari alat-alat yang akan digunakan. Nilai produktifitas 264,67 ton/jam atau 510.953 ton/tahun untuk alat gali muat dan 131,78 ton/jam/unit atau 254.405 ton/tahun/unit untuk alat angkut maka maka jumlah kebutuhan alat gali muat 1 (satu) unit dan alat angkut 2 (dua) unit dengan nilai keselarasan 1 (satu) yang artinya sempurna. Biaya-biaya yang harus dikeluarkan oleh Perusahaan untuk kebutuhan alat gali muat dan alat angkut untuk produksi yang meliputi biaya pengadaan alat, biaya oprasional, dan biaya gaji operator. Biaya untuk pengadaan alat secara beli sebesar Rp 2.115.300.000 dan secara sewa sebes Rp 849.600.000/tahun. Biaya oprasional alat secara beli sebesar Rp 1.137.240.248/tahun dan secara sewa sebesar Rp 1.065.240.248/tahun. Biaya gaji operator sebesar Rp 129.360.000/tahun. Biaya produksi alat gali muat dan alat angkut beli sebesar Rp 1.266.600.248/tahun dan secara sewa sebesar Rp 2.044.200.248/tahun. Analisa ekonomi alat gali muat dan alat angkut dengan nilai inflasi 3%/tahun menunjukan Kumulatif nilai NPV secara beli sebesar Rp 712.271.102.963 dan secara sewa sebesar Rp 695.245.976.224 dengan selisih sebesar Rp 17.026.129.738. nilai IRR secara beli sebesar 63,53 dan secara sewa 63,73 dengan selisih sebesar 0,2. Nilai PBP secara beli sebesar 1,58 dan secara sewa 1,56 dengan selisih 0,02.